The relationship between playing situation, defence and tackle technique in rugby union - Sewry, N.; Lambert, M.; Roode, B.; Matthews, B.; Hendricks, S.; Gerrard, B. (International Journal of Sports Science and Coaching, 2015)
Although it is known that both technical and tactical proficiency are required for success in rugby, not much is known about the interaction of these two characteristics and their association with success. The aim of this study was to describe the relationship between defence and tackle technique, and its association with tackle success, in the context of the playing situation. Tackle contact events (n=763) from the 2010 Super 14 rugby tournament were coded based on playing situation, defensive characteristics, tackle technique and tackle outcome. Then the relative risk ratio (RRR) was determined for each variable in relation to the tackle outcome. Technical characteristics associated with tackle success included head position of tackler (RRR 0.46, p=0.01), type of tackle (RRR 0.58, p<0.001) and tackler leg drive (RRR 0.43, p<0.05). In the relationship between technique and tactical components of the tackle (i.e., defence), tackle techniques proved to be more associated with tackle performance than defence. However, this is not to say that defensive strategies are not important when defending.